2022
DOI: 10.1001/jama.2022.4255
|View full text |Cite
|
Sign up to set email alerts
|

Association of COVID-19 Vaccination in Pregnancy With Adverse Peripartum Outcomes

Abstract: IMPORTANCEThere is limited comparative epidemiological evidence on outcomes associated with COVID-19 vaccination during pregnancy; monitoring pregnancy outcomes in large populations is required.OBJECTIVE To evaluate peripartum outcomes following COVID-19 vaccination during pregnancy. DESIGN, SETTING, AND PARTICIPANTSPopulation-based retrospective cohort study in Ontario, Canada, using a birth registry linked with the provincial COVID-19 immunization database. All births between December 14, 2020, and September… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
139
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(149 citation statements)
references
References 33 publications
7
139
2
1
Order By: Relevance
“…Third, our results are not generalizable to newly emerging SARS-CoV-2 variants and to pregnant women who have received immunomodulatory treatments and/or who have been vaccinated. It has been suggested very recently that vaccination may be associated with lower maternal respiratory severity without adverse peripartum outcomes [ 33 35 ]. Finally, we did not study the management of analgesia during labor in patients who were not intubated for delivery and further studies are needed to specifically address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Third, our results are not generalizable to newly emerging SARS-CoV-2 variants and to pregnant women who have received immunomodulatory treatments and/or who have been vaccinated. It has been suggested very recently that vaccination may be associated with lower maternal respiratory severity without adverse peripartum outcomes [ 33 35 ]. Finally, we did not study the management of analgesia during labor in patients who were not intubated for delivery and further studies are needed to specifically address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the subjects received the Pfizer/BioNTech or Moderna vaccines, and available data do not demonstrate adverse outcomes or side effects of vaccination during pregnancy [ 20 , 22 , 37 , 38 , 39 , 40 , 41 ]. Shimakaburo et al evaluated the outcomes of 827 completed pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies evaluated NICU admission rates after maternal vaccination, and none identified an increased risk 363842505764707478. The largest study found that overall rates of adverse newborn outcomes were lower among those born to people vaccinated during pregnancy versus those vaccinated afterwards, including lower NICU admission (11.0% v 13.3%; adjusted risk ratio 0.85, 0.80 to 0.90) 78.…”
Section: Covid-19 Vaccinesmentioning
confidence: 99%